AC to DC bridgeless SEPIC converter-based fuel cell emulator - Prajapati, Ashish; Gupta, Tripurari Das; Chaudhary, Kalpana (Institute of Advanced Engineering and Science, 2024)
Fuel cell (FC) technology is still in a growing phase and intensive research is required for its wider applications. However, the high cost of the FC stack is a major hurdle for researchers. This paper presents a new method of FC emulation done by using a Bridgeless SEPIC converter (BSC). The key features of the designed emulator are single stage AC-DC conversion, improved efficiency and nearly unity power factor at the input side. AC-DC BSC is controlled by using the coded model to emulate the behavior of FC. The emulated FC exhibits all three characteristics activation losses, ohmic losses, and concentration losses during operation. The MATLAB/Simulink background is used to implement the FC model and compile it into a C program. The real-time mathematical model is implemented by using a DSP(TMS320F28335) controller. Analysis, modeling, and control strategy of emulated FC are presented, static and dynamic behavior is validated through the 950W laboratory developed prototype.